"From the lips of the Bushmen": unpublished |xam San comments on Stow’s South African rock art copies - De Prada-Samper, J. M.; Hollmann, J. C. (Southern African Humanities, 2017)
We present previously unpublished comments made early in 1875 by Dia!kwain, a |xam man, on George William Stow’s copies of San rock paintings and engravings. The comments are contained in two overlooked documents that are part of the Bleek and Lloyd Collection housed at the University of Cape Town, South Africa. These two documents provide comments on rock paintings from South Africa’s Eastern Cape Province, and on rock engravings from the well-known site of Driekopseiland in the Northern Cape Province. We describe how Wilhelm Bleek and Lucy Lloyd, who elicited testimony from |xam San interlocutors in the 1870s and 1880s, became interested in soliciting comments on rock art. We provide a chronology of these explanatory remarks and discuss the acquisition by Lucy Lloyd of Stow’s copies. The contents of the two overlooked manuscripts—one catalogued as E1.1.8, the other a loose sheet of paper that we call the ‘Driekopseiland manuscript’ included within notebook L.V.3—are given in full together with the Stow copies on which the comments were based. We recognize that the comments themselves are data that require explanation and that Stow’s copies are not facsimiles of the rock art. We therefore provide annotations for each of the 14 Stow copies about which the comments were made and comment on the relevance of Dia!kwain’s remarks to rock art research.